2010
DOI: 10.1890/09-0660.1
|View full text |Cite
|
Sign up to set email alerts
|

Higher diversity of deposit‐feeding macrofauna enhances phytodetritus processing

Abstract: The link between biodiversity and ecosystem functioning is an important question that remains unresolved, particularly in marine systems, in which cycling of organic matter by benthic organisms is of global significance. Direct observations of specific resource use by each species in single- and multispecies communities, as quantified by stable isotopes, facilitates a mechanistic understanding of the importance of each species for ecosystem functioning. We tested the effects of altered biodiversity (species ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 46 publications
2
73
0
Order By: Relevance
“…Increased total resource use by a dominant species has been demonstrated previously for a wide range of environments (Cardinale et al 2006) and specifically for coastal echinoderms (Godbold et al 2009a). The results of Woulds et al (2007) contradict those of Karlson et al (2010), who found that higher metazoan macrofaunal species diversity (maximum number of species = 3, minimum number of species = 1) led to enhanced processing of phytodetritus. However, the results shown here from the PM are representative of larger multi-species communities (maximum number of species = 53, minimum number of species = 2) and demonstrate that dominant species in OMZs can have a significant impact on carbon processing.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Increased total resource use by a dominant species has been demonstrated previously for a wide range of environments (Cardinale et al 2006) and specifically for coastal echinoderms (Godbold et al 2009a). The results of Woulds et al (2007) contradict those of Karlson et al (2010), who found that higher metazoan macrofaunal species diversity (maximum number of species = 3, minimum number of species = 1) led to enhanced processing of phytodetritus. However, the results shown here from the PM are representative of larger multi-species communities (maximum number of species = 53, minimum number of species = 2) and demonstrate that dominant species in OMZs can have a significant impact on carbon processing.…”
mentioning
confidence: 57%
“…More recently, Karlson et al (2010) were able to mimic field conditions in the species-poor Baltic Sea in order to understand the effect of biodiversity on OM processing, using pulse-chase experiments. Those authors concluded that ecosystems with higher species diversity (maximum number of species = 3) incorporated more carbon and nitrogen, displayed more efficient trophic transfer of phytodetritus and were more productive than monocultures.…”
Section: Effect Of Linopherus Sp Nov On Ecosystem Responses To Gradmentioning
confidence: 99%
“…Bioturbation can enhance nutrient cycling by as much as 35% (Gutiérrez, 2011), and nutrients derived in this way can contribute up to 80% of those required by pelagic primary producers (Dale and Prego, 2002). With the exception of one study (Bolam et al, 2002), Karlson et al (2010) concluded that the positive, over-yielding relationship between benthic macrofaunal deposit feeders and phytodetrial processing observed was mainly explained by niche partitioning and/or facilitation (complementarity) rather than identity effects.…”
Section: Exchange Of Limiting Nutrientsmentioning
confidence: 92%
“…This effect is likely a combination of bioturbation and deposit feeding, but since the material was relatively fresh, bioturbation was probably the main factor. In addition, Macoma is less efficient in assimilating phytodetritus compared with, for example, Monoporeia (Karlson et al 2010).…”
Section: Hypothesis (3): Effects Of Fauna On Pigments Differ Among Famentioning
confidence: 97%